(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research aimed to identify the degree of practicing Management by Values of the Secondary Schools Managers in Lattakia City from the Teachers’ point of view in their Schools. The research also aimed to study the differences significance between the average points of the research sample of the Secondary Schools Managers according to the following variables: (sex, scientific and educational qualification, years of experience), and to achieve the objectives of this research, a questionnaire was built, consisted of (56) has been applied on a sample of (304) teachers, during the academic year of (2017 - 2018), also the current research used Descriptive analytical method and to approve the questionnaire validity, it was showed to a jury of (7) of specialized adjudicators in this domain. Its constancy was assured by applying it on a pilot sample consisted of (38) teachers, in Lattakia City through Cronbach – Alpha Reliability (0.952), and (0.974) at Spearman-Brown. The final results showed that the degree of practicing Management by Values of the Secondary Schools Managers in Lattakia City the from Teachers’ point of view, came middle rated , the result also showed no statistically significance differences in the degree of practicing Management by Values of the Secondary Schools Managers in Lattakia City of the sample members’ point of view, according to the variables (sex, and scientific and educational qualification), While there were statistically significance differences due to the Variable experience, in favor of teachers with experience of more than (10) years. The research provided some suggestions such as preparing training programs to train Secondary Schools Managers on Management by Values, also conducting other researches about applying Management by Values theory at Schools.